Using optical coherence tomography and optical coherence tomography angiography to delineate neurovascular homeostasis in migraine: a review - Chaliha, Devahuti R.; Vaccarezza, Mauro; Charng, Jason; Chen, Fred K.; Lim, Amy; Drummond, Peter; Takechi, Ryusuke; Lam, Virginie; Dhaliwal, Satvinder S.; Mamo, John C. L. (Frontiers in Neuroscience, 2024)
Migraine is one of the world's most debilitating disorders and it has recently been shown that changes in the retina can be a potential biomarker for the disease. These changes can be detected by optical coherence tomography (OCT) which measures retinal thickness, and optical coherence tomography angiography (OCTA) which measures vessel density. We searched the databases Google Scholar, ProQuest, Scopus and Web of Science, for studies in English using OCT and OCTA in migraineurs, using the search terms, "optical coherence tomography", "OCT", "optical coherence tomography angiography", "OCTA" and "migraine". We found 73 primary studies, 11 reviews and 8 meta-analyses pertaining to OCT and OCTA findings in migraineurs. They showed that migraineurs had reduced retinal thickness (via OCT), retinal vessel density and greater foveal avascular zone area (via OCTA), than controls. OCTA changes reflect a perfusion compromise occurring in migraineurs as opposed to in healthy controls. OCT and OCTA deficits were worse in migraine-with-aura and chronic migraine than in migraine-without-aura and episodic migraine. Certain areas of the eye, such as the fovea, may be more vulnerable to these perfusion changes than other parts. Direct comparison between study findings is difficult because of the hetereogeneity between the studies in terms of both methodology and analysis. Moreover, as almost all case-control studies were cross-sectional, more longitudinal cohort studies are needed to determine cause and effect between migraine pathophysiology and OCT/OCTA findings. Current evidence suggests both OCT and OCTA may serve as a retinal marker for migraineurs, and further research in this field will hopefully enable us to better understand the vascular changes associated with migraine, perhaps also providing a new diagnostic and therapeutic biomarker.